High-quality crack-free GaN epitaxial films grown on Si substrates by a two-step growth of AlN buffer layer. Issue 14 (15th March 2016) - Lin, Yunhao; Yang, Meijuan; Wang, Wenliang; Lin, Zhiting; Gao, Junning; Li, Guoqiang
Abstract : High-quality crack-free GaN epitaxial films have been grown on Si substrates by metal organic chemical vapor deposition (MOCVD) using the two-step growth of an AlN buffer layer. Abstract : High-quality crack-free GaN epitaxial films have been grown on Si substrates by metal organic chemical vapor deposition (MOCVD) using a two-step growth of AlN buffer layer. The AlN buffer layer is first grown at a V/III ratio of 2000 to obtain a 3 dimensional (3D) growth mode, and then the V/III ratio is decreased to 800 to accelerate the coalescence of the AlN grains. In comparison to the single-step AlN buffer layer growth at a fixed V/III ratio of 800, the surface morphology of the AlN buffer layer is preferably coalesced and the crystalline quality is significantly improved via the two-step growth. Furthermore, it is demonstrated that the improvement of the AlN buffer layer driven by the two-step growth method contributes greatly to improving the crystalline quality of the subsequently grown GaN epitaxial films and suppressing the generation of cracks. The excellent quality of the GaN epitaxial films is confirmed by high resolution X-ray diffraction, with full-width at half-maximum values of 338 and 390 arcsec for GaN (0002) and GaN (10–12) rocking curves, respectively. The relationships between the properties of the AlN buffer layers, including the surface morphology and crystalline quality, and the stress condition and crystalline quality of the GaN epitaxial films are elucidated. This work offers an effective approach to achieving high-quality GaN epitaxial films on Si substrates for the application of GaN-based devices.